Flotation selection of elementary sulfur from autoclave cakes after low-temperature leaching of the steering of the pyrint gold-containing concentrate; Высокие технологии в современной науке и технике (ВТСНТ-2017) - Ivanik S. A. Svetlana Alexandrovna (Химические технологии и биотехнологии, 2017)
Заглавие с титульного экрана